Putative Auxin and Light Responsive Promoter Elements From the Tomato spotted wilt tospovirus Genome, When Expressed as cDNA, Are Functional in Arabidopsis - Zhai, Ying; Peng, Hao; Neff, Michael M.; Pappu, Hanu R. (Frontiers in Plant Science, 2019)
Members of the virus order Bunyavirales cause serious diseases in animals, humans and plants. Family Tospoviridae in this order contains only one genus Orthotospovirus, and members in this genus exclusively infect plants. Tomato spotted wilt tospovirus (TSWV) is considered one of the most economically important plants viruses. Little is known about the regulatory elements in the TSWV genome. Here we show that, when in the cDNA form, the 5’-upstream region of the TSWV-coded GN/GC gene (pGN/GC) possesses putative cis-regulatory elements, including an auxin responsive element (AuxRE) for binding of auxin response factors (ARFs), as well as a circadian clock-associated 1 (CCA1) protein binding site (CBS). Due to the lack of a reverse genetics system, we verified the functionality of these elements in Arabidopsis. pGN/GC showed light-suppressive promoter activity in transgenic Arabidopsis, and mutation in the CBS was sufficient to switch the activity to light inducible. Additionally, exogenous auxin treatments repressed the promoter activity of both wild type and CBS-mutated pGN/GC. Mutation in AuxRE in both promoters abolished their sensitivity to auxin. As transcriptional repressors, both CCA1 and ARF2 were able to bind to pGN/GC directly. To our knowledge, this is the first report that a 5’-terminal sequence of an RNA virus has light-and hormone-responsive promoter activities when expressed as cDNA in host plant’s nuclear background. Our findings suggest new clues on the possible origin, evolution and function of the TSWV genomic sequence and its non-coding regions.